Trichoscopic Features of Lichen Planopilaris versus Frontal Fibrosing Alopecia: A Systematic Review - Shreya K. Gowda; Enzo Errichetti; Biswanath Behera; Vishal Thakur (Dermatology Practical & Conceptual)
Introduction: Lichen planopilaris (LPP) and frontal fibrosing alopecia (FFA) are primary scarring alopecias that few authors consider the same entity, and some consider them different.